2018
DOI: 10.19080/jetr.2018.03.555601
|View full text |Cite
|
Sign up to set email alerts
|

What is the Role of Race and Ethnicity in the Development Of Thionamide-Induced Neutropenia?

Abstract: Thionamides are anti-thyroid drugs (ATD) used to treat autonomous thyrotoxicosis. Although efficacious, these medications carry a risk of neutropenia or agranulocytosis. Some risk factors for ATD-induced neutropenia have been identified, including dose, age, and female sex, but the role of race and ethnicity has not been well studied. We hypothesize that there will be no effect of race or ethnicity on the change in Absolute Neutrophil Count (ANC) following initiation of ATD therapy.Data from the Electronic Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The absence of information on ethnicity is a key point that prevents true generalisability to the general population, as Ehrhart et al suggested in a 2018 article [30]. Ethnicity is not reported in any study, and as they are all conducted in East Asian countries, it can be problematic to assume these results will hold true in the UK, further hindering the strength of its evidence towards its application in the NICE guideline.…”
Section: Primary Study Resultsmentioning
confidence: 99%
“…The absence of information on ethnicity is a key point that prevents true generalisability to the general population, as Ehrhart et al suggested in a 2018 article [30]. Ethnicity is not reported in any study, and as they are all conducted in East Asian countries, it can be problematic to assume these results will hold true in the UK, further hindering the strength of its evidence towards its application in the NICE guideline.…”
Section: Primary Study Resultsmentioning
confidence: 99%
“…In the end, survey responses were collected and stored electronically for an anonymous analysis. The survey questions were addressed: (1) confirmation of eligibility and consent question; (2) location of residence and practice; (3) specialty; (4) career stage; (5) several patients with hyperthyroidism have been seen in clinic within the previous 12 months; (6) their perception of the frequency of agranulocytosis in patients receiving antithyroid medications; (7) what method(s) are practiced in educating patients about the risk of agranulocytosis when they are receiving antithyroid medications; (8) what they perceive as the common symptoms of agranulocytosis that patients using antithyroid medications may experience, and they should be warned about? ; (9) assuming that there are no other indications, if and when measurements of WBC count in patients using antithyroid medications are requested in the clinic; and finally, (10) if a patient on ATDs develops suspicious symptoms, what would be the most efficient facility to deal with this?…”
Section: Setting and Designmentioning
confidence: 99%
“…However, an estimate cannot be made precisely since it is influenced by ethnicity. 8 The serious side effects of ATDs have unpredictable timing and no well-defined risk factors. Therefore, patient education remains critical in managing patients receiving this treatment.…”
Section: Introductionmentioning
confidence: 99%